2013
DOI: 10.1016/j.ajpath.2013.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Novel Proteolytic Microvesicles Released from Human Macrophages after Exposure to Tobacco Smoke

Abstract: Cigarette smoking damages the extracellular matrix in a variety of locations, leading to atherosclerotic plaque instability and emphysematous lung destruction, but the underlying mechanisms remain poorly understood. Here, we sought to determine whether exposure of human macrophages, a key participant in extracellular matrix damage, to tobacco smoke extract (TSE) induces the release of microvesicles (MVs; or microparticles) with proteolytic activity; the major proteases involved; and the cellular mechanisms tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 68 publications
1
110
0
Order By: Relevance
“…Li et al (2013) noted that CSE exposure of monocytes and monocyte-derived macrophages induced a threefold rise in EV-associated matrix metalloproteinase (MMP) 14-dependent gelatinolytic and collagenolytic activity. Folkesson et al (2015) found that, when exposed to CSE, neutrophil-like HL60 cells secreted EV-associated and proteolytically active a disintegrin and metalloproteinase (ADAM)10 and ADAM17.…”
Section: Extracellular Vesicles-associated Proteolytic Enzymesmentioning
confidence: 99%
“…Li et al (2013) noted that CSE exposure of monocytes and monocyte-derived macrophages induced a threefold rise in EV-associated matrix metalloproteinase (MMP) 14-dependent gelatinolytic and collagenolytic activity. Folkesson et al (2015) found that, when exposed to CSE, neutrophil-like HL60 cells secreted EV-associated and proteolytically active a disintegrin and metalloproteinase (ADAM)10 and ADAM17.…”
Section: Extracellular Vesicles-associated Proteolytic Enzymesmentioning
confidence: 99%
“…Moreover, in vitro exposure of macrophages to tobacco smoke can directly induce the release of a mix of microparticles and exosomes carrying gelatinolytic and collagenolytic activities, mainly through the protease MMP14. These vesicles may be novel mediators of clinically important matrix destruction in smokers [77].…”
Section: Metabolic Syndrome (Mets)mentioning
confidence: 99%
“…Microparticles are also derived from other cell types, such as epithelial and inflammatory cells, but their roles are less well defined. For example, cigarette smoke stimulates the release of microparticles that have proteolytic activity (MMP14) from macrophages in vitro [103]. Endothelial microparticles containing miRNAs are increased in age-related vascular diseases, including atherosclerosis, hypertension and congestive cardiac failure [104,105].…”
Section: Micrornas and Microparticlesmentioning
confidence: 99%